2021
DOI: 10.3390/molecules26092733
|View full text |Cite
|
Sign up to set email alerts
|

Stevia Genus: Phytochemistry and Biological Activities Update

Abstract: The Stevia genus (Asteraceae) comprises around 230 species, distributed from the southern United States to the South American Andean region. Stevia rebaudiana, a Paraguayan herb that produces an intensely sweet diterpene glycoside called stevioside, is the most relevant member of this genus. Apart from S. rebaudiana, many other species belonging to the Stevia genus are considered medicinal and have been popularly used to treat different ailments. The members from this genus produce sesquiterpene lactones, dite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 262 publications
(300 reference statements)
0
13
0
Order By: Relevance
“…In particular, the chemical composition of S. aristata was published by Zdero et al [46] in which beyerene derivatives and other terpenoids were reported. In vitro antiparasitic efficacy has been described for many compounds belonging to these groups [13,[47][48][49]. Interestingly, the effect of the sesquiterpene lactone eupatoriopicrin was determined on an in vivo model of T. cruzi infection [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the chemical composition of S. aristata was published by Zdero et al [46] in which beyerene derivatives and other terpenoids were reported. In vitro antiparasitic efficacy has been described for many compounds belonging to these groups [13,[47][48][49]. Interestingly, the effect of the sesquiterpene lactone eupatoriopicrin was determined on an in vivo model of T. cruzi infection [50].…”
Section: Discussionmentioning
confidence: 99%
“…Extracts and isolated compounds from the Stevia species have been shown to have a variety of biological activities. The majority of them have antioxidant, antiparasitic, antiviral, anti-inflammatory, and antiproliferative properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stevia genus is characterized by the presence of sesquiterpene lactones, diterpenoids and flavonoids, among other phytochemical groups (Borgo et al ., 2021). Anti-parasitic activity has been described for many compounds belonging to these groups (Sanchez Alberti et al ., 2018; Boniface and Ferreira, 2019; Sessa et al ., 2020; Sülsen, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Plants from the Stevia genus (Asteraceae) are a potential source of anti-protozoal and anti-microbial compounds (Ruiz-Ruiz et al ., 2017; Borgo et al ., 2021). Recently, it has been shown that dichloromethane extracts of Stevia species presented a significant activity on Trypanosoma cruzi epimastigotes (Beer et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Estafiatin 1 is a major characteristic terpenoid component of Achillea nobilis L. and Stevia alpina Griseb [ 5 , 6 , 7 , 8 ]. Achillea nobilis L. is considered renewable plant raw material that has a sustainable operational reserve, which makes it possible to obtain the biologically active sesquiterpene lactone estafiatin on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%